Desolvation of Peptide Bond by O to S Substitution Impacts Protein Stability. Issue 47 (20th October 2021) - Khatri, Bhavesh; Raghunathan, Shampa; Chakraborti, Sohini; Rahisuddin, R.; Kumaran, S.; Tadala, Raghu; Wagh, Padmakar; Priyakumar, U. Deva; Chatterjee, Jayanta
Abstract: Amino acid side chains are key to fine‐tuning the microenvironment polarity in proteins composed of polar amide bonds. Here, we report that substituting an oxygen atom of the backbone amide bond with sulfur atom desolvates the thioamide bond, thereby increasing its lipophilicity. The impact of such local desolvation by O to S substitution in proteins was tested by synthesizing thioamidated variants of Pin1 WW domain. We observe that a thioamide acts in synergy with nonpolar amino acid side chains to reduce the microenvironment polarity and increase protein stability by more than 14 °C. Through favorable van der Waals and hydrogen bonding interactions, this single atom substitution significantly stabilizes proteins without altering the amino acid sequence and structure of the native protein. Abstract : A C=O to C=S substitution in the amide bond dramatically alters the water structure around the thioamide bond, ultimately reducing the microenvironment polarity. The increased hydrophobicity of the modified peptide bond is utilized to amplify the thermostability of proteins by this single atom substitution.